Cholera epidemic amidst the COVID-19 pandemic in Moroto district, Uganda: Hurdles and opportunities for control - Philip Orishaba; Marc Sam Opollo; Christine Nalwadda; Allan Muruta; Issa Makumbi; Kenneth Kabali; Anne Nakinsige; Phillip Lotee; Samuel I. Okware; Godfrey Bwire (PLOS Global Public Health, 2022)
Introduction On 21st March 2020, the first COVID-19 case was detected in Uganda and a COVID-19 pandemic declared. On the same date, a nationwide lockdown was instituted in response to the pandemic. Subsequently, more cases were detected amongst the returning international travelers as the disease continued to spread across the country. On May 14th, 2020, a cholera epidemic was confirmed in Moroto district at a time when the district had registered several COVID-19 cases and was in lockdown. This study aimed to describe the cholera epidemic and response activities during the COVID-19 pandemic as well as the hurdles and opportunities for cholera control encountered during the response. Materials and methods In a cross-sectional study design, we reviewed Moroto district’s weekly epidemiological records on cholera and COVID-19 from April to July 2020. We obtained additional information through a review of the outbreak investigation and control reports. Data were analyzed and presented in frequencies, proportions, attack rates, case fatality rates, graphs, and maps. Results As of June 28th, 2020, 458 cases presenting with severe diarrhea and/or vomiting were line listed in Moroto district. The most affected age group was 15–30 years, 30.1% (138/458). The females, 59.0% [270/458], were the majority. The Case Fatality Rate (CFR) was 0.4% (2/458). Whereas home use of contaminated water following the vandalization of the only clean water source in Natapar Kocuc village, Moroto district, could have elicited the epidemic, implementing COVID-19 preventive and control measures presented some hurdles and opportunities for cholera control. The significant hurdles were observing the COVID-19 control measures such as social distancing, wearing of masks, and limited time in the community due to the need to observe curfew rules starting at 6.00 pm. The opportunities from COVID-19 measures complementary to cholera control measures included frequent hand washing, travel restrictions within the district & surrounding areas, and closure of markets. Conclusion COVID-19 preventive and control measures such as social distancing, wearing of masks, and curfew rules may be a hurdle to cholera control whereas frequent hand washing, travel restrictions within the district & surrounding areas, and closure of markets may present opportunities for cholera control. Other settings experiencing concurrent cholera and COVID-19 outbreaks can borrow lessons from this study.